2021
DOI: 10.5897/err2021.4169
|View full text |Cite
|
Sign up to set email alerts
|

Online learning during the COVID-19 pandemic from the perspectives of English as foreign language students

Abstract: This study aimed at exploring the advantages and disadvantages of the online learning system implemented during COVID-19 Pandemic from English as foreign language (EFL) students' perspective. To achieve the objectives of the study, qualitative approach was used. The sample of the study consisted of 20 students who were chosen purposely from the World Islamic Sciences and Education University in Amman, Jordan. A semi-structured interview was used to collect data and Braun and Clarke's thematic approach (2006) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…It is simple to instruct numerous students at any time and wherever in the world using online instructing methods (Dhawan, 2020;Gacs et al, 2020). Therefore, students do not have to commute to school, which saves time (Alodwan, 2021;Okyar, 2023) and helps them to manage their time more effectively (Khalil et al, 2020). Consequently, online education is appreciated because of its location and time flexibility (Gonçalves et al, 2020;Le & Tran, 2023;Ludwig & Tassinari, 2023;Mather & Sarkans, 2018;Song et al, 2004).…”
Section: Opportunities Of Online Educationmentioning
confidence: 99%
See 3 more Smart Citations
“…It is simple to instruct numerous students at any time and wherever in the world using online instructing methods (Dhawan, 2020;Gacs et al, 2020). Therefore, students do not have to commute to school, which saves time (Alodwan, 2021;Okyar, 2023) and helps them to manage their time more effectively (Khalil et al, 2020). Consequently, online education is appreciated because of its location and time flexibility (Gonçalves et al, 2020;Le & Tran, 2023;Ludwig & Tassinari, 2023;Mather & Sarkans, 2018;Song et al, 2004).…”
Section: Opportunities Of Online Educationmentioning
confidence: 99%
“…Consequently, online education is appreciated because of its location and time flexibility (Gonçalves et al, 2020;Le & Tran, 2023;Ludwig & Tassinari, 2023;Mather & Sarkans, 2018;Song et al, 2004). Online education has also been reported to be cost-effective (Alodwan, 2021, Dahmash, 2020Ludwig & Tassinari, 2023;Okyar, 2023).…”
Section: Opportunities Of Online Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to that, foreign language teachers need to gear their teaching style to suit the needs of the learners who needed their self-esteem to be lifted in order to benefit most from the foreign language classes. Talal (2021) suggested that teachers can assist in the de-emergence of social isolation among learners by building rapport through small talks. Class sizes is also one of the indispensable elements in crafting enjoyment among the foreign language learners.…”
Section: Pedagogical Implications and Suggestions For Future Researchmentioning
confidence: 99%